2011
DOI: 10.1590/s1806-00132011000300014
|View full text |Cite
|
Sign up to set email alerts
|

Assistência de enfermagem e dor em pacientes ortopédicos na recuperação anestésica, no Brasil

Abstract: Rev Dor. São Paulo, 2011 jul-set;12(3):265-69 RESUMO JUSTIFICATIVA E OBJETIVOS: A dor traz prejuí-zos na recuperação do paciente submetido à cirurgia ortopédica. O objetivo deste estudo foi descrever as informações relacionadas à experiência dolorosa de pacientes em pós-operatório de cirurgias ortopédicas na sala de recuperação pós-anestésica (SRPA) que podem contribuir para a assistência de Enfermagem. CONTEÚDO: Trata-se de estudo com abordagem qualitativa, as fontes para a coleta das informações foram as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 3 publications
0
9
0
6
Order By: Relevance
“…No período pós-operatório, as cirurgias ortopédicas estão diretamente associadas com a dor de intensidade moderada a forte. A experiência dolorosa, neste período, é citada pelos pacientes, por isso, é necessária uma atenção especial para a analgesia a ser administrada (PAULA et al, 2011).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…No período pós-operatório, as cirurgias ortopédicas estão diretamente associadas com a dor de intensidade moderada a forte. A experiência dolorosa, neste período, é citada pelos pacientes, por isso, é necessária uma atenção especial para a analgesia a ser administrada (PAULA et al, 2011).…”
Section: Discussionunclassified
“…Os benefícios da analgesia adequada são certos, uma vez que, esta melhora a qualidade do atendimento, proporciona maior bem estar ao paciente, controla o estresse físico e permite avanços em sua recuperação (PAULA et al, 2011;GIANCOLI et al, 2012).…”
Section: Discussionunclassified
“…Qualified professionals to control pain have higher possibilities of assuring a more humanized assistance to patients. The holistic care involving pain management of cancer patients submitted to surgery involves the need for consideration of biological, emotional and behavioral aspects of such patients 5,10 : "Pain is considered a syndrome resulting from physical and emotional aspects which have to be taken care of " 11 . The consideration exposed by the authors is confirmed by the statement that the development of resilience in the abilities of being, having, being able to and wanting to, contributing for a reflection about cancer patients' assistance 12 .…”
Section: Contentsmentioning
confidence: 99%
“…Cancer pain control should be evaluated in a unique way, being individual for each patient and with responsibility, for the assistance to be adequate. When dealing with aspects involving pain management teaching as the fifth vital sign, the qualification of professors and students about the subject significantly contributes for pain management 5 . So, in this category, it has been observed that nursing care with regard to pain involves the consideration of the subjectivity of pain perception by cancer patients.…”
Section: Contentsmentioning
confidence: 99%
See 1 more Smart Citation